2019
DOI: 10.3389/fpls.2018.01914
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Sources of Resistance to Seed Weevils (Bruchus spp.) in a Faba Bean Germplasm Collection

Abstract: Seed weevils (Bruchus spp.) are major pests of faba bean, causing yield losses, and affecting marketability. Our objective was to identify stable sources of resistance to seed weevil attacks, determine the climatic factors that most influenced its incidence and its relationship with some phenological and agronomic traits. The accessions “BOBICK ROD115,” “CÔTE D’OR,” “221516,” and “NOVA GRADISKA” showed increased resistance to penetration and development of larvae. Other accessions such as “QUASAR,” “109.669,” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 39 publications
(46 reference statements)
2
25
1
Order By: Relevance
“…The next steps in our research will be to perform Quantitative Trait Locus (QTL) analyses to identify potential candidate genes for resistance to faba bean seed weevils in Pop1 and Pop3. In a previous work 35 , we reported that the male parents NOVA GRADISKA and QUASAR present partial resistance to the attack of bruchids. Differences in parental responses to bruchids attacks suggested distinct resistance mechanisms in the two accessions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The next steps in our research will be to perform Quantitative Trait Locus (QTL) analyses to identify potential candidate genes for resistance to faba bean seed weevils in Pop1 and Pop3. In a previous work 35 , we reported that the male parents NOVA GRADISKA and QUASAR present partial resistance to the attack of bruchids. Differences in parental responses to bruchids attacks suggested distinct resistance mechanisms in the two accessions.…”
Section: Discussionmentioning
confidence: 86%
“…NOVA GRADISKA and QUASAR have previously been reported as resistant to the faba bean weevil (Bruchus spp.) attack 35 . All segregating recombinant populations used for mapping were made of F 3 plants produced by single seed descent (SSD) of F 2 plants.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it is essential to evaluate accessions for the potential traits (de Carvalho et al ., 2013; Anglin et al ., 2018; Byrne et al ., 2018). In legumes (including cowpea), information on bruchid resistance is crucial for the utilization of germplasm in crop improvement and screening of diverse germplasm is an important step to identify sources of bruchid resistance (Somta et al ., 2008; Upadhyaya et al ., 2011; Carrillo-Perdomo et al ., 2019). The current study was undertaken to screen a diverse set of cowpea germplasm comprising landraces, elite lines, registered germplasm and primitive cultivars for C. maculatus .…”
Section: Discussionmentioning
confidence: 99%
“…A combination of seed traits in cultivated genotypes has been reported to lower infestation levels and thereby contribute to bruchid resistance (Tripathi et al ., 2013). Cowpea germplasm collections are known to exhibit wide variability for seed traits (Lattanzio et al ., 2005), and screening of diverse germplasm accessions is essential to identify novel sources of bruchid resistance (Carrillo-Perdomo et al ., 2019). However, only limited efforts have been made to screen germplasm collections for their trait variability.…”
Section: Introductionmentioning
confidence: 99%
“…Grass pea is cultivated for its seeds as a healthy food (Lambein et al 2019) and feed (Smulikowska et al 2008), as well as for fodder (Singh and Roy 2013). It is a hardy and resilient crop (Campbell 1997) that is rarely affected by pests and diseases (Rahman et al 1995) and is one of the most climate and environmental change tolerant legumes (Kislev 1989;Yunus and Jackson 1991;Chowdhury and Slinkard 2000;Vaz Patto et al 2006).…”
Section: Grass Peamentioning
confidence: 99%